Nilai-Nilai Kesejahteraan Negara Indonesia Dengan Keadilan Berlandaskan Pancasila - Agustina, Elsa; Dewi, Dinie Anggraeni (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2023)
The writing of this article using qualitative method is research based on the theory and data available. The sources cited in this paper are journals, articles, and thesis. The writing aims to disseminate the values contained in Pancasila to be implemented by Indonesian citizens in their daily lives. Everyone wants prosperity in his life be it society, nation, and state. The reference point of welfare is social justice. Pancasila as the basis of the state as a guide in daily life will realize the welfare of umun in Indonesia. Problems in the nation's internal affairs also become one of the impacts that must be solved by returning to the values of Pancasila. Pancasila only has five principles but can unite the state of Indonesia because between the precepts complement each other.